Improving Poetry Writing Skills with Contextual Teaching and Learning Model assisted by Audiovisual Media for Fifth Grade Students - Fitriani, Lilik; Adi, Tuti Tarwiyah; Nurhasanah, Nina (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This study originated from a problem in grade V students of SDN Bojong 03, namely the low student learning outcomes in the material of poetry writing skills. Writing poetry as a skill needs to be trained so that the expected results can be achieved, one of the efforts to improve poetry writing skills is to apply the Contextual Teaching and Learning (CTL) model assisted by audiovisual media. The purpose of this study is to explain the process and results of improving poetry writing skills with the Contextual Teaching and Learning (CTL) model assisted by audiovisual media. This research was conducted at SDN Bojong 03 in class V with a total of 26 students. This research method uses a classroom action research method conducted over three cycles. Each cycle consists of four stages, namely, planning, implementation, observation or observation and reflection. Each cycle was carried out for three meetings, one meeting lasted 2x35JP. The results of this study have increased learning outcomes in each cycle. In cycle I, the score ≥ 70 was 12 students with a percentage of 48%, in cycle II, the number of students who received a complete score ≥ 70 was 17 students, and the third cycle, the number of students who were complete was 22 students with a percentage of 85% and the average score was 77. Based on the increase in learning outcomes, it can be concluded that the use of Contextual Teaching and Learning (CTL) models is assisted by audiovisual media.